1987
DOI: 10.1080/03015521.1987.10425586
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of a phenological model (PETE) to assist insect pest control in apple orchards in Canterbury, New Zealand

Abstract: An evaluation was conducted of a model (PETE) for predicting the phenology of codling moth (Cydia pomonel/a L.) and the lightbrown apple moth (Epiphyas postvittana (Walker)) in apple orchards in Canterbury, New Zealand. Validation data consisted of adult flights recorded with pheromone traps for codling moth, and bait trap catches and the occurrence of eggs and larvae recorded by destructive sampling of apple tree clusters for lightbrown apple moth. Key events in the life history of both pests occurred over ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The Danish information suggests that populations at high latitudes may respond similarly to the present larger dataset. However, in New Zealand (≈39° S latitude), where codling moth has only a single generation per year, moth emergence and phenology appear to be quite different, and researchers have suggested that those populations may have a different overwintering state related to relatively mild winter temperatures and fewer chilling degree‐days than found in most apple production regions in the northern hemisphere …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Danish information suggests that populations at high latitudes may respond similarly to the present larger dataset. However, in New Zealand (≈39° S latitude), where codling moth has only a single generation per year, moth emergence and phenology appear to be quite different, and researchers have suggested that those populations may have a different overwintering state related to relatively mild winter temperatures and fewer chilling degree‐days than found in most apple production regions in the northern hemisphere …”
Section: Discussionmentioning
confidence: 99%
“…Firstly, polynomials can cause artifacts near the ends of the dataset, especially if the data fall outside the range of latitude used to generate the regression. Secondly, these types of site are almost certainly relatively abnormal for apple, pear or walnut production and likely have issues related to diapause induction/termination or insufficient chilling units for codling moth . Finally, the authors did not find literature or original data paired with temperature data that would allow them to check how well the model works in the southern hemisphere (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…For each data set, we estimated the difference between the date of the peak in first spring flight and DDRP predictions of the average date of first spring egg laying. This event was chosen because peak flight would likely happen at about the same time that peak egg laying is occurring [63]. Additionally, we used DDRP to calculate the number of degree-days that accumulated between the last peak fall flight and first peak spring flight for four winters (2011-2012, 2012-2013, 2013-2014, and 2019-2020), which should serve as a rough estimate of generation time.…”
Section: Case Studiesmentioning
confidence: 99%
“…Phenological models have been important tools used to improve the management of codling moth, Cydia pomonella (L.), in many apple producing areas worldwide (Barros-Parada, Knight, & Fuentes-Contreras, 2015;Blago, 1992;Chappell, Kennedy, & Walgenbach, 2015;Damos et al, 2018;Jones et al, 2013;Knight, 2007;Riedl, Croft, & Howitt, 1976;Samietz, Graf, Höhn, Schaub, & Höpli, 2007;Tomkins, Penman, Chapman, & Worner, 1987). However, there are always concerns regarding the applicability of available prediction models under new conditions and different scenarios (Blomefield & Giliomee, 2011;Kuhrt, Samietz, & Dorn, 2006).…”
mentioning
confidence: 99%